Isolation and genotyping of some skin germs from patient samples imported to Tishreen University Hospital /Syria/ - الدالي حسن; أميمة ناصر; عماد حداد; تميم حماد (Latakia University Journal -Medical Sciences Series, 2023)
Some germs were isolated and genotyped from pathological samples (wound swab، skin edema، bronchial lavage، cervical swab، pus) imported to Tishreen University Hospital in Lattakia Governorate during the period from (1/9-30/12/2021) depending on the Characteristics of bacterial culture، Gram staining، microscopy، and group plate test Three isolates of Gram-positive cocci were obtained، and according to biochemical tests، Analytical Profile Index Staph، API، isolates were genotyped to (A) Staphylococcus aureus (A) Staphylococcus aureus، Gram-positive، and the second type (B) Staphylococcus epidermis، Staphylococcus epidermidis، Gram-positive cocci، while the third type، Streptococcus pyogenes (C)، Streptococcus pyogenes، Gram-positive، during an incubation period that lasted (24-72). ) Hour، at a temperature of (37) Celsius